Female Political Modalities and Representation Dynamics: A Study of the 2019 Legislative Elections - Sidik Firmadi; Hilal Ramdhani; Riska Sarofah; Nursila Abdul (Yayasan Keluarga Guru Mandiri, 2026)
Women's political presence in Indonesia is constrained despite a 30 percent gender quota, as the legislation applies only to the candidate nomination phase and does not guarantee electoral success. The disparity is apparent in the 2019 parliamentary election in Banjar City, West Java, where only one woman was elected out of 30 seats. This study analyses the political mechanisms that enabled a female candidate with limited resources to attain electoral success in a highly competitive, patriarchal local environment. Using a qualitative descriptive methodology, data were gathered through document analysis, electoral records from the General Election Commission, and comprehensive interviews with women voters in Pataruman District. The examination focused on four types of political capital: social, cultural, political, and economic. The results indicate that social capital was the most critical factor, as ongoing community involvement and women-focused networks fostered significant voter trust and grassroots support. Deficiencies in cultural and economic capital were effectively mitigated through the strategic use of gender narratives and volunteer-driven campaigns. Moderate political capital was bolstered by party affiliation and women-led mobilization. The study suggests that women's electoral success is not exclusively reliant on robust or elite political resources but may also be attained via the smart use of moderate approaches. This study advances the literature by redefining political capital as a dynamic, context-sensitive resource and offering novel insights into strategies to improve women's participation in local legislatures.